Participation in organized sports activities and evaluation of self-esteem among children in puberty - Martinaș Florentina-Petruța; Voinea Nicolae-Lucian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
In sports activities, the knowledge of mental characteristics, character traits or the level of individual sensory and cognitive processes, have become decisive factors of sports performance. The many transformations suffered by individuals during puberty, age, physical changes or social context can affect self-perception. The aim of this paper is to highlight the relationship between self-esteem and the practice or non-practice of an organized sports activity, among children in puberty. We assume that practicing an organized sports activity can influence the values of self-esteem among children in puberty.In the present paper they were evaluated 160 subjects, boys (N=57) and girls (N=103), aged 11-14, practitioners (N= 140, rugby= 20, football= 20, basketball= 20, volleyball= 20, martial arts= 20, dance= 20, tennis= 20) and non-practitioners (N= 20) of sports activities. To assess self-esteem, we applied the ASSI questionnaire (2007) standardized on the Romanian population, which also targeted the close poles of this dimension, self-depreciation and infatuation. Interpretations of individual questionnaire results were generated by the PsihoProfile platform, entered into the database and statistically analyzed using the program IBM SPSS Statistics20. The obtained results highlight statistical differences between practicing and non-practicing subjects of organized sportive activities, but also differences between the types of activities and the gender of the subjects. Therefore, practicing sports activities in an organized setting can positively influence the values of self-esteem among children in puberty.